Pendampingan Pembuatan Nomor Induk Berusaha (NIB) UMKM di Desa Rejoso, Kecamatan Rejoso, Kabupaten Nganjuk, Provinsi Jawa Timur - Hendra Maulana; Chulaisy Meidianto; Naufal Hilmy Fauzan; Ismiatul Ilmiah; Fatimah Azzahra; Adisty Nadyra Kristianti (SAFARI :Jurnal Pengabdian Masyarakat Indonesia, 2023)
Business legality is an important aspect that needs to be done by every business person, especially Micro, Small, and Medium Enterprises (MSMEs). From the data collected by the group of 64 thematic KKN UPN “Veteran” East Java 2023, they found that UMKM actors in Rejoso Village, Rejoso District, Nganjuk Regency, most of UMKM do not have business legality. This paper will present the results of community service activities that have been carried out related to assistance in making business Identification Numbers (NIB). This service aims to share insights and practice making NIB so that MSME actors can have and benefit from the legality of the business.